PWE-087 Temporal change and phenotypic pattern of liver function tests can distinguish ischaemic hepatitis from drug induced liver injury– a large 6 year retrospective cohort analysis. (17th June 2017) - Gulliver, J; Dalton, H; Aithal, G; Hussaini, H
Abstract : Introduction: Both drug induced liver injury (DILI) and ischaemic hepatitis (IH) present acutely and neither have specific diagnostic tests. Therefore, diagnosis and hence the management relies upon signature pattern of manifestations. We hypothesised that the temporal pattern in the change of bilirubin and alanine transaminase (ALT) may help distinguish those patients with IH compared to DILI. Method: Retrospective single centre analysis of biochemical data from 68 sequential patients with IH over 84 months (mean age 65 ±SEM 1.1 year, 63% male) and 66 patients with DILI (67 ±SEM 1.9 year; 46% male) over a 79 month period. Patients were identified from the hospital biochemistry and outpatient Jaundice Hotline (JHL) databases. The diagnosis of DILI based on the use of established causality assessment methods (RUCAM). IH cases were defined as patients with an ALT level >1000 iu/L and exclusion of those with elevated paracetamol levels, autoimmune or viral hepatitis and DILI on clinical review. Comparative ALT and bilirubin data between the two groups was analysed from 14 days prior to and 35 days after presentation (day 0) using unpaired t tests for unequal variance. Results: The IH cohort had a higher rise in index ALT (1321 ±SEM166 iu/l) compared to those with DILI (319±32; p<0.0001) but by day 14 this difference was significantly reversed (79±7 vs 211±44; p<0.006). The mean bilirubin in the DILI vs IH group was significantly higher at presentation (95±11 vs 21±2 umol/L) with a peak at day 14 of 140±23 umol/L with only a slow fall by day 35 to 100±22 umol/L in the DILI group.The data for change in bilirubin and ALT over the study period are shown in Figures 1 and 2. Conclusion: These data support the hypothesis that patients with ischaemic hepatitis demonstrate a rapid rise and fall in ALT following an ischaemic insult and subsequently have a relatively short recovery phase compared to those with DILI. Conversely, patients with severe DILI exhibit a high index bilirubin. These presenting biochemical features and temporal changes may help distinguish DILI from IH. Disclosure of Interest: None Declared